KEPADATAN POPULASI THRIPS Thrips sp. (Thysanoptera:Thripidae) PADA TANAMAN CABAI DI KAMPUNG BATU KECAMATAN DANAU KEMBAR KABUPATEN SOLOK - Sari, Neng; Jasmi, Jasmi; Pratiwi, Putri (STKIP PGRI Sumbar, 2014)
Â Thrips populations sp . in Kampung Batu Solok District of Twin Lakes in pepper can reduce the production of vegetables . One of the vegetables contained in this stone village area is chili . The chili is a community that is relatively important and very popular all over the world , and loved by the community chili has low calories and contains vitamin C which is high for a chili fruit contains 20 calories with no fat at all In this regard it has done research on the population density of Thrips sp . ( Thysanoptera : Thripidae ) in pepper in Kampung Batu Twin Lakes District of Solok which aims to determine the population density of Thrips sp . in pepper This study was conducted in September-November 2013, with a descriptive survey method is by way of direct collection against Thrips sp. the research sites. The area used as a study about 30x 20 m. Sampling was conducted on pepper plants already have flowers and pepper plants that have fruit. Physical environmental factors that will be measured are temperature, humidity , and soil moisture . From the research conducted characteristics Thrips sp. found in pepper in Kampung Batu subdistrict Twin Lakes ie, black slim body shape , and jet black , and the wings are fringed and have segmented bodies . The results were obtained an average population density of Thrips sp. on pepper plants that have gained interest of 3.87 individuals / stem and the fruit of pepper plants that have gained 2.92 individual / stem.